Government regulation of public enterprises - Shahob, Mokhtar (Journal of the Belarusian State University. Economics, 2018)
The article analyses and summarizes the world experience in the management of public enterprises of the country. The author outlines sectoral, dual and centralized models and reports about successful Chinese experience of dividing the state functions as an owner and a regulator.
Keywords: state enterprises; public sector; corporate governance; management models of state enterprises